Boosting Employee Performance through Empowerment and Job Satisfaction in Indonesia: Meningkatkan Kinerja Karyawan melalui Pemberdayaan dan Kepuasan Kerja di Indonesia - Ardi Saputro; Sumartik (Universitas Muhammadiyah Sidoarjo, 2024)
This research investigates the impact of Employee Empowerment, Work Environment, and Work Stress on Employee Performance, with Job Satisfaction as an intervening variable at PT. Rui Xue International. Despite the recognized importance of these factors, there is limited understanding of their combined effects in the context of Indonesian companies. The study employs a quantitative survey method with a descriptive approach, encompassing a sample of 61 employees selected through saturation sampling. Data were collected via questionnaires and analyzed using Partial Least Squares (PLS) path analysis with Smart PLS Version 3.0 software. Findings reveal that Employee Empowerment and Work Environment positively influence Employee Performance and Job Satisfaction. Work Stress does not significantly affect Employee Performance directly but significantly impacts Job Satisfaction, which in turn affects Employee Performance. The results underscore the importance of fostering employee empowerment and a conducive work environment to enhance performance, while managing work stress through improving job satisfaction. These insights contribute to the strategic management of human resources in similar organizational settings. Highlight: Employee empowerment significantly enhances both job satisfaction and employee performance. A positive work environment greatly impacts job satisfaction and performance. Work stress affects performance indirectly through job satisfaction. Keywords: Employee Empowerment, Work Environment, Work Stress, Employee Performance, Job Satisfaction